Regulatory Competition Between Central Govemment Agencies And Local Government In Indonesia: Studv Oflocal Law Review in 2007-2009 - Dr. Achmad Nurmandi, M.Sc. (Fak. Hukum UNIBRA, 2010)
This paper is aimed to investigate and analyze 250 cancelled local law review and its legal opinion as issued by the Home Affairs Ministry and Finance Ministry 2007-2009. The study found that there was regulatory competition not only between local law and law or government regulation, but also between local law and central government agencies. This competition was taken place on objects that have to be regulated and licensing authority. Decree of local law quash suit by the Ministry of Home Affairs is becoming legal standing debate. Decree of ministry as a central authoritative regulator extensively regulates the locally local government activity at the local area. The study also found that decision space of local government in decentralization is narrower than central government one. Theoretical contribution of the study revealed that different ranges of choice within and between tipology of deconcentration, decentralization or devolution.